A Site‐Isolated Organoruthenium‐/Organopalladium‐Bifunctionalized Periodic Mesoporous Organosilica Catalyzes Cascade Asymmetric Transfer Hydrogenation and Suzuki Cross‐Coupling. Issue 10 (9th September 2014) - Zhang, Dacheng; Xu, Jianyou; Zhao, Qiankun; Cheng, Tanyu; Liu, Guohua
Abstract An important challenge in asymmetric cascade reactions is solving the intrinsic incompatibility of two types of distinct organometallic complexes that participate in a one‐pot reaction. Herein, we develop an organoruthenium‐/organopalladium‐bifunctionalized periodic mesoporous organosilica and realize one‐pot cascade reactions of Ru‐catalyzed asymmetric transfer hydrogenation and Pd‐relay‐catalyzed cross‐coupling of haloacetophenones and arylboronic acids to various chiral biaryl alcohols, with quantitative conversions and up to 98 % enantioselectivity in an aqueous medium. This characteristics is attributed to the site‐isolated, uniformly distributed, well‐defined single‐site palladium and ruthenium active species. Furthermore, the heterogeneous catalyst is conveniently recovered and reused repeatedly for eight times without loss of its catalytic activity, showing particular attractiveness for practicing organic transformation.